SASTRA PROFETIK KUNTOWIJOYO - Aminudin Rifai (Sunan Kalijaga State Islamic University Yogyakarta, 2009)
Prophetic literature is, basically, a work of transcendental and mystical spirit because it comes from the deific values. In additions, it tends to change the course of the civilization to a better route because of its messianic spirit. Kuntowijoyo (1943–2005) is one of the prophetic poets with his touch on blending the social themes with historical activism in his works. The balance between social and spiritual world; between deific saturation and problems faced by the society; between the life before and after death, between religious and historical experience are depicted gracefully in his works. The propheticism in Kuntowijoyo works could be traced by using Riffatere’s semiotics.